Virtual I/O Forwarding for Cloud-based HPC Applications - Llopis, Pablo; Martin, G.; Bergua, B.; Carretero, J. (2012 IEEE 10th International Symposium on Parallel and Distributed Processing with Applications, 2012)
In this work we present a flexible I/O virtualization solution, which is evaluated and compared to similar I/O forwarding technologies. Furthermore, we present a distributed I/O forwarding backend architecture which allows for complex, multi-host setups that can aim for different I/O strategies such as power proportionality and higher throughput.